Online Control of Smart Inverter for Photovoltaic Power Generation Systems in a Smart Grid - Huang, Kuo-Hua; Chao, Kuei-Hsiang; Sun, Zhi-Yao; Liao, Yu-Hsiang (Frontiers in Energy Research, 2022)
The main purpose of this paper is to engage in research on a grid-connected photovoltaic (PV) power generation system smart inverter. The research content includes a smart maximum power point tracking (MPPT) controller and an inverter with power regulation. First, use the PSIM software package to establish the simulation environment of the grid-connected photovoltaic power generation system, and use the Sanyo HIP-186BA19 photovoltaic module to form a 744W system for simulation. In order to enable the photovoltaic module array (PVMA) to output the maximum power under different solar insolation and ambient temperature, the architecture is based on the extension theory-based smart MPPT method to improve the dynamic response and steady-state performance of photovoltaic power generation systems and compared to perturb and observed (P＆O) MPPT. When the sunshine is 1,000W/m2, the photovoltaic power generation system adopts the extension theory-based maximum power tracking method. The time required to track the maximum power point is only 0.32 seconds and the steady-state ripple is only 4.127W. However, using the traditional P&O method requires 0.741 seconds to track the maximum power point, and the steady-state ripple reaches 18.131W. Thus, the dynamic response speed of the maximum power tracking method proposed is 50% faster than that of the P&O method. The steady-state performance is also better compared to the P&O method. At the same time, a simple proportional-integral (PI) controller is used to regulate the DC-link voltage, output voltage and current of the inverter to make the voltage of the grid-connected point is stable at an effective value of 220V. Then, the voltage-power control technology is added to the photovoltaic grid-connected inverter, and a simple proportional-integral controller is used to regulate the output of the smart inverter reactive power to improve the power quality of grid voltage. Finally, simulation and experimental results are used to verify the effectiveness of the regulation performance of the developed smart inverter.